2004
DOI: 10.1124/jpet.104.077883
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with an Angiotensin-Converting Enzyme Inhibitor and an Angiotensin II Receptor Blocker Synergistically Suppresses Chronic Pancreatitis in Rats

Abstract: We recently demonstrated that both lisinopril and candesartan, an angiotensin-converting enzyme inhibitor and angiotensin II type 1 receptor blocker, respectively, attenuate pancreatic inflammation and fibrosis in male Wistar Bonn/Kobori (WBN/Kob) rats. The purpose of the present study was to assess whether combination therapy with low doses of both, ineffective when given alone, might synergistically exert protective effects. Lisinopril, candesartan, or a combination of both in drinking water was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…[13][14][15] The renin-angiotensin system plays an important role in causing SMC fibrosis, and angiotensin II type I receptor blockers and angiotensin-sconverting enzyme inhibitors can ameliorate SMC fibrosis and extend the life span of SMCs in animal models. [16][17][18][19] Tankyrase 1 also has a similar effect. 14,15 This study determined that a decrease in erectile function coincided with the downregulation of SMC proliferation and SMC/CF proportions in diabetic ED rats and that icarisid II could ameliorate these effects.…”
Section: Discussionmentioning
confidence: 82%
“…[13][14][15] The renin-angiotensin system plays an important role in causing SMC fibrosis, and angiotensin II type I receptor blockers and angiotensin-sconverting enzyme inhibitors can ameliorate SMC fibrosis and extend the life span of SMCs in animal models. [16][17][18][19] Tankyrase 1 also has a similar effect. 14,15 This study determined that a decrease in erectile function coincided with the downregulation of SMC proliferation and SMC/CF proportions in diabetic ED rats and that icarisid II could ameliorate these effects.…”
Section: Discussionmentioning
confidence: 82%
“…Animal studies, however, are not consistent with ARB-related damage. Studies have shown cardesartan suppresses inflammation and fibrosis in rats [22] and a combination of an ACE inhibitor and an ARB synergistically suppresses chronic pancreatitis [23]. The mechanisms by which pancreatitis is induced by ACE inhibitors or ARBs are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, blockade of the receptors for PDGF, TGF-β, and angiotensin II, as well as blockade of the intracellular signaling pathways downstream of these receptors, is likely to provide therapeutic benefit (17,51,76,108). In this regard, there are in vivo experiments showing the importance of the angiotensin II system in the development of pancreatic fibrosis (64,108).…”
Section: Potential Treatments For Pasc Disordersmentioning
confidence: 99%
“…In this regard, there are in vivo experiments showing the importance of the angiotensin II system in the development of pancreatic fibrosis (64,108). There are also several reports from in vitro experiments using PaSCs that show key roles in the activation and/or proliferation process for MAPK pathways, in particular, ERK1/2, p38 kinase, and JNK (50,52,53,66,109,110); PI3K and PKC (111); PPARγ (36,112); NADPH oxidases (our unpublished observations); and ethanol metabolism to acetaldehyde (18).…”
Section: Potential Treatments For Pasc Disordersmentioning
confidence: 99%
See 1 more Smart Citation